The Role Of The Indonesian Waqf Board (bwi) In Productive Waqf In Gorontalo Province - Miranti Midu; Fatmawati N. Halid; Syaifuddin Podungge; Hussein 'Azeemi Abdullah Thaidi; Ibah Misbah (Department of Sharia Financial Management, 2025)
Non-Indexed Publication